Can you spot a troll? Teaching information literacy through conversations about social media attacks. Issue 1 (2nd January 2021) - Lawless, Brandi
Abstract : With increasing social media attacks on scholarship and individual academics, educators must be prepared to talk to their students openly about skewed threats from the ideological right. This assignment opens up dialogue against such attacks by introducing core tenets of information literacy in conversation with an instructor's academic work. The activity promotes open dialogue in ways that humanize those instructors who are the target of such attacks while teaching key aspects of information literacy. Course : Introduction to Communication, Introduction to Media Studies, Critical Thinking. Objectives: (1) Evaluate credibility in online communication (2) Understand the major tenets of information literacy (3) Develop strategies for critical reading of arguments in scholarly work (4) Create dialogue between students and instructors